STATISTICAL ANALYSIS OF PUBLIC PARTICIPATION IN THE PRIMARY REAL ESTATE MARKET OF MOSCOW REGION - Maxim A. Fomin (Статистика и экономика)
This article focuses on the comprehensivestatistical analysis of the development ofthe primary real estate market of Moscowregion, in particular the participation ofstate bodies in the sphere of constructionof various properties, both residential andnon-residential buildings - health, education, culture, transport, communications,etc. the main problems and prospects ofdevelopment of the construction complexof Moscow region on the basis of freshstatistical data.